Discovering Elements and Developing Strategies to Implement the Tailored Care Education for Patients with Diabetes through A Systematic Review - Satriya Pranata; Shu-Fang Vivienne Wu; Tsae-Jyy Tiffany Wang; Shu-Yuan Liang; Yeu-Hui Chuang; Kuo-Cheng Lu; Khoiriyah Khoiriyah (Diponegoro University, 2022)
Background: The popular intervention in avoiding diabetes complications in several countries is health education. However, a tailored care education approach based on the phenotyping of patients' abilities, preferences, cultural orientation is still unclear. Purpose: To discover elements and develop strategies to implement tailored care education for patients with diabetes through a systematic review. Methods: This two-stage systematic review was conducted. The first stage was primary search and assessed the quality of articles followed by discovering elements and developing strategies of tailored care education for patients with diabetes in the second stage. Results: This review included 44 out of 1421 articles that were published in English and focused to discuss on tailored care education for patients with diabetes. Self-management, patient preferences, patient value, interprofessional collaboration, tailored support, glycemic control, and patient centre were among the elements. These factors were utilized to develop seven step strategies for providing diabetes patients with tailored care education. Conclusion: Traditional clinical intervention, decision-making, and future research trends are predicted to be transformed into a personalized care approach. Establishing the effectiveness of tailored care education programs in reducing the risk of diabetes complications among diabetic patients is needed.